2016
DOI: 10.1371/journal.pone.0156103
|View full text |Cite
|
Sign up to set email alerts
|

Multicentric Genome-Wide Association Study for Primary Spontaneous Pneumothorax

Abstract: Despite elevated incidence and recurrence rates for Primary Spontaneous Pneumothorax (PSP), little is known about its etiology, and the genetics of idiopathic PSP remains unexplored. To identify genetic variants contributing to sporadic PSP risk, we conducted the first PSP genome-wide association study. Two replicate pools of 92 Portuguese PSP cases and of 129 age- and sex-matched controls were allelotyped in triplicate on the Affymetrix Human SNP Array 6.0 arrays. Markers passing quality control were ranked b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…[30][31][32] Approximately 10% of patients with PSP have a positive family history of pneumothorax, 33,34 although no specific genetic mutations have been associated with sporadic PSP. 35 Loeys-Dietz syndrome. [36][37][38] In these syndromes, pneumothorax is believed to result from the lower tensile strength of the visceral pleural.…”
Section: Pathophysiologymentioning
confidence: 99%
“…[30][31][32] Approximately 10% of patients with PSP have a positive family history of pneumothorax, 33,34 although no specific genetic mutations have been associated with sporadic PSP. 35 Loeys-Dietz syndrome. [36][37][38] In these syndromes, pneumothorax is believed to result from the lower tensile strength of the visceral pleural.…”
Section: Pathophysiologymentioning
confidence: 99%
“…To investigate whether nonapical lung cysts might herald FLCN mutations among patients with spontaneous pneumothorax, Johannesma and colleagues screened 40 patients with nonfamilial and familial spontaneous pneumothorax with chest CT imaging; indeed, all three subjects with cysts below the carina had FLCN mutations (11). To determine whether common genetic variants play a role in pneumothorax risk, Sousa and colleagues performed a genomewide association study of spontaneous pneumothorax (12). No SNPs met the Bonferroni correction threshold in the replication dataset.…”
Section: Sporadic Pneumothoraxmentioning
confidence: 99%
“…LINC00824, located at chromosome 8q24.21, is also known as LINC01263. Genome-wide association studies reported that LINC00824 polymorphisms were associated with primary spontaneous pneumothorax and rheumatoid arthritis [ 18 , 19 ]. Here, we firstly found that rs699467 in LINC01414 and rs7815944 in LINC00824 might be protective factors for COPD occurrence, while LINC01414 rs298207 increased the risk of COPD in the whole population.…”
Section: Discussionmentioning
confidence: 99%